An Analysis of the Determinants Influencing Internal Auditors’ Ability to Detect Fraud in Indonesian State-Owned Enterprises - Muhammad Arsyad; Amiruddin; Rahmawati HS (International Journal of Business and Quality Research, 2026)
This study examines persistent challenges in fraud detection within Indonesian State-Owned Enterprises (BUMN), despite the formal establishment of internal audit mechanisms. Motivated by recurring large-scale corruption cases that remained undetected over extended periods, the study aims to identify and empirically analyse the key determinants influencing internal auditors’ ability to detect and disclose fraud. A mixed-methods explanatory design was employed, integrating quantitative and qualitative approaches. Data were collected from 85 internal auditors through structured questionnaires, supported by in-depth interviews and Focus Group Discussions (FGDs) involving auditors from BUMN, the Financial and Development Supervisory Agency (BPKP), and the Inspectorate General. Quantitative data were analysed using multiple linear regression, while qualitative data were examined through thematic analysis and visualized using a mind mapping approach. The results reveal that six determinants auditor competence, independence and objectivity, management support, internal control systems, organizational culture, and audit technology have positive and significant effects on fraud detection capability, explaining 70.9% of the variance (R² = 0.709). Auditor competence and independence emerge as the most influential factors. This study proposes a determinant-based model of internal audit effectiveness and highlights the need for integrated reforms to strengthen audit capability and accountability within BUMN.